2018
DOI: 10.1140/epjc/s10052-018-5955-1
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the SELEX–LHCb double-charm baryon conflict: the impact of intrinsic heavy-quark hadroproduction and supersymmetric light-front holographic QCD

Abstract: In this paper we show that the intrinsic heavyquark QCD mechanism for the hadroproduction of heavy hadrons at large x F can resolve the apparent conflict between measurements of double-charm baryons by the SELEX fixed-target experiment and the LHCb experiment at the LHC collider. We show that in fact both experiments are compatible, and that both can be correct. The observed spectroscopy of double-charm hadrons is in agreement with the predictions of supersymmetric light front holographic QCD.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…For more details, see refs. [34,37]. The effective supersymmetric properties of QCD can be used to identify the structure of the heavy quark mesons, baryons and tetraquark states [34].…”
Section: Supersymmetric Hadron Spectroscopy For Heavy Quarksmentioning
confidence: 99%
“…For more details, see refs. [34,37]. The effective supersymmetric properties of QCD can be used to identify the structure of the heavy quark mesons, baryons and tetraquark states [34].…”
Section: Supersymmetric Hadron Spectroscopy For Heavy Quarksmentioning
confidence: 99%
“…In Ref. [19], the authors showed that the intrinsic heavy-quark QCD mechanism for the hadroproduction of heavy hadrons at large x F can resolve the apparent conflict between measurements of double-charm baryons by the SELEX fixedtarget experiment and the LHCb experiment at the LHC collider.…”
Section: Introductionmentioning
confidence: 99%
“…We hope that, by the development of experimental facilities, we will be able to detect other members of the doubly heavy baryons. The production mechanism of doubly heavy baryons has an important place in the literature [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Naturally, a doubly heavy baryon can be produced using a two-step procedure: i-) in a hard interaction, a double heavy diquark is produced pertur-batively, ii-) and then it is transformed to the baryon within the soft hadronization process [34].…”
Section: Introductionmentioning
confidence: 99%
“…The SELEX experiment has already been shut down and its puzzle on Ξ cc observation, e.g., its measured production rate is much larger than most of the theoretical predictions [51,52], remains unresolved. The intrinsic charm production mechanism may solve this puzzle [26]. And we still need more accurate fixed-target experimental data to clarify the issue.…”
Section: Introductionmentioning
confidence: 99%